Passive Design of Buildings for Extreme Weather Environment - S.N. Al-Zubaidy; S. Tokbolat; R. Tokpatayeva (International Journal of Renewable Energy Development, 2013)
Buildings account for nearly 40% of the end-use energy consumption and carbonemissions globally. Buildings, once built, are used at least for several decades. The building sectortherefore holds a significant responsibility for implementing strategies to increase energyefficiency and reduce carbon emissions and thus contribute to global efforts directed towardmitigating the adverse effects of climate change. The work presented in this paper is a part ofcontinuing efforts to identify, analyze and promote the design of low energy, sustainable buildingswith special reference to the Kazakhstan locality. Demonstration of improved environmentalconditions and impact on energy savings will be outlined through a case study incorporating apassive design approach and detailed computational fluid dynamics analysis for an existingbuilding complex. The influence of orientation and configuration is discussed with reference toenergy efficiency and associated wind comfort and safety. The effect of these aspects on energyconsumption and comfortable wind environment has been assessed using CFD analysis and provedto be affective. Single building and multiple building configurations have been analyzed andcompared. According to the findings, multiple building configurations have better wind conditionswhen compared with a single standing building. With respect to orientation the former one shouldbe modeled with the fully surrounded side of a “box” opposite to the predominant wind directionwhereas the latter one should be located with the rear side opposite to the wind direction. Thus,results indicated that there is a considerable influence of passive design and orientation on energyefficiency, wind comfort and safety. Careful consideration and application of the findings canpotentially lead to considerable decrease of energy consumption and, therefore, allow savingmoney and the environment at the same time.